Fast curve fitting algorithm for parameter evaluation in lightning impulse test technique - Pattanadech, Norasage; Yutthagowith, Peerawut (My University, 2015)
This paper proposes a fast curve fitting technique for the evaluation of the base curve of lightning impulse voltage and current. The proposed method is based on the waveform parameter estimation employing a numerical integration and linear least square method. This method is derived from an ordinary differential equation. The proposed algorithm is able to fit the base curve of lightning impulse voltage and current. The formula of the base curve is in the complex form of two exponential functions. The proposed form is superior to the conventional real exponential form, since it can be rewritten in a real conventional form used for fitting the impulse voltage or in a damped/undamped sinusoidal form with phase shift for fitting the impulse current. The decomposition base curve procedure was tested with some impulse voltage and current waveforms collected from the test data generator attached with IEC 61083- 2 (2013). The waveform parameters evaluated by the proposed method are compared with those recommended by the standards. The proposed method shows the better performance in computation time than the conventional method recommended by the standards. Due to no requirement of iteration in the proposed curve fitting method, the computation time is much shorter than the conventional iterative method. Moreover, the utilization of the established method does not allow the recorded impulse waveform distortion. Besides, the developed algorithm technique can be done easily with markedly accuracy and noise immunity. For the aforementioned reasons, there is no doubt that the proposed technique is a superior one for impulse parameter evaluation.
Keywords: Curve fitting; Fitting; Lightning; Mathematical model; Oscillators; Oscilloscopes; Standards